Hubungan Tingkat Pengetahuan, Sikap dengan Perilaku Warga dalam Pemenuhan Komponen Rumah Sehat - Purwaningrum, Sri Wulan; Rini, Titien Setiyo; Saurina, Nia (Universitas Ahmad Dahlan, 2018)
Introduction: Health development directed to increased awareness, willness and ability to live healthy for every single people so that public health can be realized. In line with Health Ministry of Republic Indonesia, Puskesmas has aimed to support development of national health. According to information from Puskesmas Sukorejo in Kelurahan Sukorejo, Kecamatan Bojonegoro there are only 17% healthy house from 1.412 families and most of them throw away household waste to the river. Method: This research used an observational analytic study with cross sectional design. The population in this research was rural people in Sukorejo Village, Kecamatan Bojonegoro, which were 60 people. Data analysis has been done by using univariate analysis and bivariate analysis. The study was conducted in March 2015. Results: Based on statistical test table showed correlation coeffisien that is 0.414 with value Significant (Ï) that is 0.000 which show that value of Ï<0.05. Conclusion: There was a strong and positive relationship between attitudes with the behavior of citizens in the fulfillment of healthy house components. The attitude contributed to the incidence of citizen behavior in the fulfillment of healthy house components of 0.414 or 41.4%.